Turnaround Strategies And Sustainable Development Of Smes In Rivers State - Macaulay Wegwu Enyindah (Genius Journals, 2024)
This study investigates the relationship between turnaround strategies and development of SMEs in Rivers State. In carrying out this investigation, the researcher believed that the problems of SMEs in Rivers State include their inability to access finance and credit facilities which constrained their ability to invest in infrastructure, technology, human capital development, and many others. As guides to the investigation, the researcher stated four hypotheses that were tested empirically in respect to financial restructuring, organizational restructuring, and sustainable development within Small and MediumSized Enterprises (SMEs) in Rivers State, Nigeria. Using a sample of 150 respondents from ten SMEs, the research employed Spearman's rank order correlation coefficient to analyze data collected through structured questionnaire. The findings revealed that organizational restructuring significantly enhances both social and environmental sustainability, financial restructuring showed a significant relationship only with social sustainability. These results underscore the importance of adopting holistic restructuring strategies that integrate financial stability with social and environmental objectives. The study concluded that there is a significant relationship between turnaround strategies and development of SMEs in Rivers State. It was therefore recommended that SMEs to focus on turnaround strategies involving integrated restructuring, stakeholder engagement, and continuous monitoring to achieve comprehensive sustainable development.
Keywords: Financial restructuring; Organizational restructuring; turnaround strategies